2011
DOI: 10.2478/v10184-010-0011-8
|View full text |Cite
|
Sign up to set email alerts
|

Mericarp micromorphology and anatomy of Salvia hedgeana Dönmez, S. huberi Hedge and S. rosifolia Sm. (section Salvia Hedge, Lamiaceae)

Abstract: Mericarp (nutlet) micromorphology and pericarp structure of three morphologically similar endemic Salvia species; Salvia hedgeana, S. huberi and S. rosifolia were investigated using LM, SEM and TEM. Salvia hedgeana has larger mericarps and abscission scars than S. huberi and S. rosifolia. Mericarp length to width ratio ranges from 1.11 in S. hedgeana to 1.60 in S. huberi. Mericarp shape is mainly ovoid, rarely broadly ovoid in S. hedgeana, and oblong in S. huberi. The mericarp surface sculpturing pattern in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Mericarp characters, such as mericarp size, shape and color, and ornamentation pattern of the surface, are useful in identifying species and generic levels [24]. The macro-and micromorphology of Salvia mericarps present useful discriminating characters that are adequate for identifying species [19,[21][22][23][24]. The study on mericarp morphology of 15 Turkish Salvia taxa belonging to the section Hymenosphace Benth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mericarp characters, such as mericarp size, shape and color, and ornamentation pattern of the surface, are useful in identifying species and generic levels [24]. The macro-and micromorphology of Salvia mericarps present useful discriminating characters that are adequate for identifying species [19,[21][22][23][24]. The study on mericarp morphology of 15 Turkish Salvia taxa belonging to the section Hymenosphace Benth.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, a moderately mucilaginous reaction was observed on the pericarp surface of S. pilifera. Büyükkartal et al [23] investigated mericarps of three Turkish endemics S. hedgeana Dönmez, S. huberi Hedge and S. rosifolia Sm. belonging to the section Salvia and found that S. huberi differed from the other species in having translucent-milky white opaque mucilage with fibres or radiating cordons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The groups of two-staminate genera, as in Salvia, and fourstaminate genera of Salviinae, as in Lepechinia and Chaunostoma, can be separated from each other and from other Lamiaceae genera by differences in pericarp structure (Ryding, 2010). Variations in the pericarp structure have been pointed out to be helpful in the identification of morphologically similar Salvia species (Büyükkartal et al, 2011). In this study, the pericarp of S. napifolia is observed to be significantly thicker than that of S. russellii.…”
Section: Discussionmentioning
confidence: 54%
“…Ultrastructural studies on the pericarp have been carried out in various genera of the family Lamiceae and have proved the usefulness of pericarp characters for species and generic level in the family (Wagner, 1914;Bilimovitsch, 1935;Wojciechowska, 1958Wojciechowska, , 1961aWojciechowska, , b, 1966Wojciechowska, , 1972Makarova, 1967, Hedge & Lamond, 1968Hedge, 1970;Witztum, 1978;Ryding, 1992aRyding, , b, 1993aRyding, , b, 1995Ryding, , 2001Ryding, , 2010Budantsev, 1993a, b;Budantsev & Lobova, 1997;Duletić-Lauševic & Marin, 1999;Mosquero, Juan, & Pastor, 2002;Moon & Hong, 2006). However, there have been only a few studies on the pericarp ultrastructure of the genus Salvia (Wojciechowska, 1958(Wojciechowska, , 1966Hedge, 1970;Oran, 1997;Ryding, 2010;Büyükkartal, Kahraman, Çölgeçen, Doğan, & Karabacak, 2011;Hassan & Al. Thobaiti, 2014).…”
Section: Introductionmentioning
confidence: 99%